(untitled) (Advances in Applied Mathematics and Mechanics, 2021)
Symmetric Taylor-Görtler-like vortices at Re=3200 and 5000 in 3D rectangular cavities with a moving top lid are studied numerically and tested with a spanwise aspect ratio of 1 : 1 : L, where L=1, 2, 3. Solutions are obtained by solving the momentum equations and the continuity equations using the consistent splitting scheme. The code presented here was ported to the Parallel Interoperable Computational Mechanics System Simulator (PICMSS). Stable solutions are obtained as limit cases of the transients.